Determination of estradiol valerate in pharmaceutical preparations and human serum by flow injection chemiluminescence. (9th July 2012) - Liu, Wenwen; Xie, Liangxiao; Liu, Hongshuang; Xu, Shichao; Hu, Bingcheng; Cao, Wei
ABSTRACT: A novel method for the detection of trace estradiol valerate (EV) in pharmaceutical preparations and human serum was developed by inhibition of luminol chemiluminescence (CL) by estradiol valerate on the zinc deuteroporphyrin (ZnDP)‐enhanced luminol‐K3 Fe(CN)6 chemiluminescence system. Under optimized experimental conditions, CL intensity and concentration of estradiol valerate had a good linear relationship in the ranges of 8.0 × 10 ‐8 to 1.0 × 10 ‐5 g/mL. Detection limit (3 σ ) was estimated to be 3.5 × 10 ‐8 g/mL. The proposed method was applied successfully for the determination of estradiol valerate in pharmaceutical preparations and human serum and recoveries were 97.0‐105.0% and 95.5‐106.0%, respectively. The possible mechanism of the CL system is discussed. Copyright © 2012 John Wiley & Sons, Ltd.